Consistently positive effect of species diversity on ecosystem, but not population, temporal stability - Xu, Qianna; Yang, Xian; Yan, Ying; Wang, Shaopeng; Loreau, Michel; Jiang, Lin; Chase, Jonathan (Ecology letters, 2021)
Despite much recent progress, our understanding of diversity–stability relationships across different study systems remains incomplete. In particular, recent theory clarified that within‐species population stability and among‐species asynchronous population dynamics combine to determine ecosystem temporal stability, but their relative importance in modulating diversity‐ecosystem temporal stability relationships in different ecosystems remains unclear. We addressed this issue with a meta‐analysis of empirical studies of ecosystem and population temporal stability in relation to species diversity across a range of taxa and ecosystems. We show that ecosystem temporal stability tended to increase with species diversity, regardless of study systems. Increasing diversity promoted asynchrony, which, in turn, contributed to increased ecosystem stability. The positive diversity–ecosystem stability relationship persisted even after accounting for the influences of environmental covariates (e.g., precipitation and nutrient input). By contrast, species diversity tended to reduce population temporal stability in terrestrial systems but increase population temporal stability in aquatic systems, suggesting that asynchronous dynamics among species are essential for stabilizing diverse terrestrial ecosystems. We conclude that there is compelling empirical evidence for a general positive relationship between species diversity and ecosystem‐level temporal stability, but the contrasting diversity–population temporal stability relationships between terrestrial and aquatic systems call for more investigations into their underlying mechanisms. Our meta‐analysis showed that ecosystem temporal stability tended to increase with species diversity, regardless of study systems. Increasing diversity promoted asynchronous dynamics among species, which, in turn, contributed to increased ecosystem stability. By contrast, species diversity tended to reduce population stability in terrestrial systems but increase population stability in aquatic systems, suggesting that asynchronous dynamics are particularly important for stabilizing diverse terrestrial ecosystems.